Entropy of flexible liquids from hierarchical force-torque covariance and coordination: Thermodynamics 2017 Conference - Higham, Jonathan; Chou, Szu-Yu; Gräter, Frauke; Henchman, Richard H. (Molecular physics, 2018)
New theory is presented to calculate the entropy of a liquid of flexible molecules from a molecular dynamics simulation. Entropy is expressed in two terms: a vibrational term, representing the average number of configurations and momentum states in an energy well, and a topographical term, representing the effective number of energy wells. The vibrational term is derived in a hierarchical manner from two force-torque covariance matrices, one at the molecular level and one at the united-atom level. The topographical term comprises conformations and orientations, which are derived from the dihedral distributions and coordination numbers, respectively. The method is tested on 14 liquids, ranging from argon to cyclohexane. For most molecules, our results lie within the experimental range, and are slightly higher than those by the 2PT method, the only other method currently capable of directly calculating entropy for such systems. As well as providing an efficient and practical way to calculate entropy, the theory serves to give a comprehensive characterisation and quantification of molecular structure.
Published online: 30 Apr 2018
Gesehen am 14.01.2020